2008
DOI: 10.1109/tnb.2008.2000144
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Fibers Are Compatible With Mammalian Cells and Neurons

Abstract: We demonstrate the biocompatibility of carbon nanotube fibers (CNFs) fabricated from single-wall carbon nanotubes. Produced by a particle-coagulation spinning process, CNFs are "hair-like" conductive microwires, which uniquely combine properties of porous nanostructured scaffolds, high-area electrodes, and permeable microfluidic conduits. We report that CNFs are nontoxic and support the attachment, spreading, and growth of mammalian cells and the extension of processes from neurons in vitro. Our findings sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…In general, the present results are in keeping with previous reports showing that CNTs have low toxicity, low immunogenicity, and good biocompatibility (16). For example, a previous study found no apparent changes in cell viability of cardiomyocytes, even when a higher dose of CNTs was used (17).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In general, the present results are in keeping with previous reports showing that CNTs have low toxicity, low immunogenicity, and good biocompatibility (16). For example, a previous study found no apparent changes in cell viability of cardiomyocytes, even when a higher dose of CNTs was used (17).…”
Section: Discussionsupporting
confidence: 93%
“…Conflicting results regarding clearance, distribution, and toxicity are reported in the literature (14,16), which is likely due to the characteristics of the material used, i.e., differences in the physical properties and structure, as well as pretreatment processes, surfaces, aggregation, purity, functionalization, experimental protocol, administration form, and concentration. Thus, the toxicity must be assessed individually for each type of CNT-based biocomposite and in each physiological system involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of recent literature using CNTs as cell growth substrates and effects on biological activity is shown in Table 1 [8][9][10][11][12][13][14][17][18][19][24][25][26][27] of the Supplementary data. An examination of these literature shows that both MWNT and SWNT are able to perform well as bioactive supports for many cell types and that aligned MWNTs can influence cell alignment.…”
Section: Resultsmentioning
confidence: 99%
“…However the in-vivo study is a very different and more complex environment than on synthetic nanotube substrates as we have here or other similar studies. Single-wall CNTs have been shown to support the growth of carcinoma cells, fibroblasts, neuronal cells [17,18] and osteoblasts [19].…”
Section: Introductionmentioning
confidence: 99%